MAKNA AKUNTBILITAS DANA LASCARYA: PELAPORAN SUMBANGAN SUKARELA WARGA BANJAR PADA PERAYAAN UPACARA HARI RAYA NYEPI - Nyoman Budhiswara Krishna; Maria Eugenia Hastuti (CALYPTRA, 2018)
This study aims to explain the occurrence of a phenomenon that is understanding the meaning of accountability in celebration Nyepi Day. This study explores the meaning of cultural accountability in organizations that are not profit-oriented to present the financial statements of each period can be accounted for. Main research Question in this research is How is the Accountability significance of the Lascarya Fund: Reporting the Voluntary Donation of Banjar Citizens that fit the culture of Hari Raya Nyepi? The results of this study indicate that the accountability related to the Banjar X banjar residents' contribution by reading the accountability report in the evaluation meeting followed by the indigenous people only, but that is enough to represent the accountability carried out to control the funds donated by the citizens by actively participating indigenous Banjar X who came to the evaluation meeting.